2015
DOI: 10.1002/jcp.24947
|View full text |Cite
|
Sign up to set email alerts
|

Alpha‐Lipoic Acid Promotes Osteoblastic Formation in H2O2‐Treated MC3T3‐E1 Cells and Prevents Bone Loss in Ovariectomized Rats

Abstract: Alpha-lipoic acid (ALA), a naturally occurring compound and dietary supplement, has been established as a potent antioxidant that is a strong scavenger of free radicals. Recently, accumulating evidences has indicated the relationship between oxidative stress and osteoporosis (OP). Some studies have investigated the possible beneficial effects of ALA on OP both in vivo and in vitro; however, the precise mechanism(s) underlying the bone-protective action of ALA remains unclear. Considering this, we focused on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 69 publications
3
30
0
Order By: Relevance
“…Our observation from the current study and data from other experiments (Fu et al, 2015) demonstrate that ovariectomy results in an elevation of Nox4 gene expression and protein synthesis as well as an increase in ROS production. Considering that FLL could scavenge free radical oxygen (Jeong et al, 2016) and elevate antioxidant enzyme levels in human neuroblastoma SH-SY5Y cells (Ju et al, 2012), we then investigated whether FLL exhibited antioxidant activities in osteoporotic rats.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Our observation from the current study and data from other experiments (Fu et al, 2015) demonstrate that ovariectomy results in an elevation of Nox4 gene expression and protein synthesis as well as an increase in ROS production. Considering that FLL could scavenge free radical oxygen (Jeong et al, 2016) and elevate antioxidant enzyme levels in human neuroblastoma SH-SY5Y cells (Ju et al, 2012), we then investigated whether FLL exhibited antioxidant activities in osteoporotic rats.…”
Section: Discussionsupporting
confidence: 83%
“…In the previous study, we demonstrated that treatment of OVX rats with FLL markedly improved bone mechanical strength and bone microarchitectures (Guo et al, 2016a). Moreover, inhibition of Nox4 activity and expression further contributed to protection of osteoblasts against H 2 O 2 insults and prevention of OVX-induced bone loss (Fu et al, 2015). Therefore, the findings of the current study may suggest that FLL exhibits bone protective effect through inhibiting ROS release via the regulation of Nox4 expression in OVX rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…H 2 O 2 , as involvement of oxidative stress, may induce the self-generation of free radicals and produce a wide range of damages including apoptosis, necrosis or autophagy of various types of cells, including osteoblast cells [2628]. In this study, MC3T3-E1 cells were exposed to H 2 O 2 to perform a model of oxidative damage, we found that treating MC3T3-E1 cells with H 2 O 2 resulted in reduction of cell viability, ROS production and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The cells were subsequently divided into 4 experimental groups [19, 20]: (1) the control group: normal glucose (5.5 mM) α-MEM alone (NG), (2) the high glucose group: high glucose (25.5 mM) α-MEM alone (HG), (3) the 0.1 mM ALA group: high glucose α-MEM + 0.1 mM ALA (HG+) and (4) the 0.2 mM ALA group: high glucose α-MEM + 0.2 mM ALA (HG++).…”
Section: Methodsmentioning
confidence: 99%